The January Anomaly: Effects of Low Share Price, Transaction Costs, and Bid‐Ask Bias - BHARDWAJ, RAVINDER K.; BROOKS, LEROY D. (Journal of Finance, 1992)
ABSTRACT The January effect is primarily a low‐share price effect and less so a market value effect. In the recent 1977–1986 period, after‐transaction‐cost raw and excess January returns are lower on low‐price stocks than on high‐price stocks. Failure of informed traders to eliminate significantly large before‐transaction‐cost excess January returns on low‐price stocks is potentially explained by higher transaction costs and a bid‐ask bias. At the least, the January anomaly found in prior tests is not persistent, and thereby, not likely to be exploitable by typical investors.